Plasma Science and Technology Basic Fundamentals and Modern Applications - Jelassi, Haikel; Benredjem, Djamel (IntechOpen, 2019)
Usually called the "fourth state of matter," plasmas make up more than 99% of known material. In usual terminology, this term generally refers to partially or totally ionized gas and covers a large number of topics with very different characteristics and behaviors. Over the last few decades, the physics and engineering of plasmas was experiencing a renewed interest, essentially born of a series of important applications such as thin-layer deposition, surface treatment, isotopic separation, integrated circuit etchings, medicine, etc. Plasma Science & Technology - Basic Fundamentals and Modern Applications presents the basic fundamentals behind plasma physics along with some of their most important modern applications.